Impact Of Digital Technology On Bsnl Employees’ Behaviour - ASLESH S. S.; Dr. C. MURALIKUMARAN (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Employees working in a private company adopt new technology easily. Employees working in private companies are implementing and learning digital technology for job security. But more or less employees working in the public sector face numerous problems in espousing and learning digital technology. This has positive or negative effects on the employee's performance, behavior and their interpersonal relationships. There are constraints and challenges but the employees need to strive to achieve whatever is possible through the resources available with the employees. Hence, the research tries to identify the impact of digital technology on BSNL employees’ behaviour in Kerala. Data was collected from fifty BSNL employees in Kerala. Hence, it is concluded that digital technology in the workplace has a positive effect on employee behaviour. The research also identified that employee behaviour has a positive effect on employee performance. The research suggested that BSNL will create a culture that encourages employees to be innovative and creative and improve employee behavior by imparting knowledge of digital technology to reduce employee stress and improve employee performance.